2009
DOI: 10.1644/09-mamm-a-002r.1
|View full text |Cite
|
Sign up to set email alerts
|

Activity Pattern Segregation of Carnivores in the High Andes

Abstract: Intraguild competition may be reduced if ecologically similar species segregate temporally. Using data from 1,596 camera-trap photos, we present the 1st quantitative analyses of the activity patterns of Andean cats (Leopardus jacobita), Pampas cats (Leopardus colocolo), culpeos (Lycalopex culpaeus), and pumas (Puma concolor) in high-altitude deserts of the Andes. We compared daily activity patterns for these carnivores with those of mountain vizcachas (Lagidium viscacia), the main prey of Andean cats. Activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 29 publications
10
84
1
8
Order By: Relevance
“…Jaguars in Amolar Mountain Ridge exhibited cathemeral behaviour, a pattern different of the observed in other areas of the Pantanal (Crawshaw & Quigley, 1991;Foster et al, 2013). Pumas were also cathemeral, which is consistent with observations of Gómez et al (2005) in Bolivia; although in Argentina, western Bolivia and Chile, pumas are crepuscular (Lucherini et al, 2009). As opportunistic predators, jaguars and pumas feed on a large variety of prey, but they mainly consume medium to large-sized prey (Emmons, 1987;Taber et al, 1997;Núñez et al, 2000;Monroy-Vilchis et al, 2009).…”
Section: Resultssupporting
confidence: 79%
“…Jaguars in Amolar Mountain Ridge exhibited cathemeral behaviour, a pattern different of the observed in other areas of the Pantanal (Crawshaw & Quigley, 1991;Foster et al, 2013). Pumas were also cathemeral, which is consistent with observations of Gómez et al (2005) in Bolivia; although in Argentina, western Bolivia and Chile, pumas are crepuscular (Lucherini et al, 2009). As opportunistic predators, jaguars and pumas feed on a large variety of prey, but they mainly consume medium to large-sized prey (Emmons, 1987;Taber et al, 1997;Núñez et al, 2000;Monroy-Vilchis et al, 2009).…”
Section: Resultssupporting
confidence: 79%
“…Culpeo activity was largely nocturnal, and this was the only period of the day when the proportion of records exceeded that expected on the basis of availability (Figure 1). This pattern resembles that reported for the High Andes by Lucherini et al (2009).…”
supporting
confidence: 90%
“…Culpeos appeared to prefer rocky areas (67.8% of photos) but they also used scrublands, as reported by Redford and Eisenberg (1992) (Table 1). All the photographs of hog-nosed skunks were taken at night, which agrees with the nocturnal habits described for this species (Donadio et al 2001, Lucherini et al 2009). Conversely, all the photographs and observations of lesser grisons were during daylight hours despite being described as cathemeral (Nowak 2005).…”
supporting
confidence: 77%
“…Closely related, morphologically similar species commonly share ecological requirements (Anderson et al 2002 ), so there is often some degree of niche differentiation to allow them to coexist (Lucherini et al 2009, Di Bitetti et al 2010, Jennings and Veron 2011. The niche complementarity hypothesis asserts that a high degree of overlap in one niche component should be associated with a low degree of overlap in at least one other niche dimension (Lucherini et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The niche complementarity hypothesis asserts that a high degree of overlap in one niche component should be associated with a low degree of overlap in at least one other niche dimension (Lucherini et al 2009 ). Our niche analyses suggested that these two closely related civet species primarily occur in evergreen forest, yet there is a tendency for them to separate spatially along an elevation gradient: the banded civet mainly occurs in lowland areas and Hose ' s civet is mostly found at higher elevations.…”
Section: Discussionmentioning
confidence: 99%